Three Theban plays antigone, Oedipus the King, Oedipus at Colonus - Sophocles (Oxford Oxford University Press, 1956)
Towering over the rest of Greek tragedy, the three plays that tell the story of the fated Theban royal family?Antigone, Oedipus the King and Oedipus at Colonus?are among the most enduring and timeless dramas ever written. Robert Fagles's authoritative and acclaimed translation conveys all of Sophocles's lucidity and power: the cut and thrust of his dialogue, his ironic edge, the surge and majesty of his choruses and, above all, the agonies and triumphs of his characters. This Penguin Classics edition features an introduction and notes by the renowned classicist Bernard Knox.
Keywords: Sophocles--Translations into English